2014
DOI: 10.1111/jvh.12222
|View full text |Cite
|
Sign up to set email alerts
|

Occult hepatitis B virus infection and hepatocellular carcinoma: a systematic review

Abstract: Occult hepatitis B (OHB) infection has been reported to play an important role in the development of hepatocellular carcinoma (HCC). In this systematic review, a significantly higher prevalence of OHB was observed in patients with HCC in the presence or absence of HCV infection when compared with control populations without HCC. Correspondingly, among adequately designed prospective studies, the cumulative probability of developing HCC was significantly greater among patients with OHB than among HBV DNA-negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 89 publications
(178 reference statements)
2
55
1
3
Order By: Relevance
“…Several reports have suggested that occult HBV is transmissible through blood transfusion and organ transplantation, and may lead to cirrhosis and/or the subsequent development of HCC. 53 This finding is also of interest, because this area is positioned in the transitional zone between the Asian and Australian biogeographical regions, where parallel evolution and genotypic adaptation have occurred in organisms ranging from microbes to plants, invertebrates, vertebrates, and primates. 24 This might be considered in the explanation of the high OHB cases in this study, because differences in the HBV-specific host immune response have been described as one of the possible mechanisms leading to occult HBV, 54 as indicated by the presence of anti-HBs in 77.5% (38/49) of OHB cases in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that occult HBV is transmissible through blood transfusion and organ transplantation, and may lead to cirrhosis and/or the subsequent development of HCC. 53 This finding is also of interest, because this area is positioned in the transitional zone between the Asian and Australian biogeographical regions, where parallel evolution and genotypic adaptation have occurred in organisms ranging from microbes to plants, invertebrates, vertebrates, and primates. 24 This might be considered in the explanation of the high OHB cases in this study, because differences in the HBV-specific host immune response have been described as one of the possible mechanisms leading to occult HBV, 54 as indicated by the presence of anti-HBs in 77.5% (38/49) of OHB cases in this study.…”
Section: Discussionmentioning
confidence: 99%
“…HCV increases HCC risk by promoting cirrhosis and causing specific genetic lesions to the infected liver cells [6] . Clinically relevant hepatitis viral infections has been shown to predispose individuals to HCC, similarly, occult hepatitis B infection has been associated with the development of HCC [7] . Higher viral loads with prolonged infections have been correlated with the occurrence of HCC and may be due to accumulated risks from chronic oncogenic damage [8] .…”
Section: Pathogenesis and Risk Factorsmentioning
confidence: 99%
“…Different virological characteristics were found in HCC patients with OBI, for example, higher frequencies of amino acidic mutations in Pre-S/S such as the presence of premature stop codons or some nucleotidic substitutions in the enhancer II region such as G1721A. The overall conclusion is that, despite the low viral load, the risk of HCC in OBI patients is high [77].…”
Section: Pathobiology and Clinical Implications Of S-escape Mutantsmentioning
confidence: 96%